• Matéria: Matemática
  • Autor: gegivanuchi
  • Perguntado 8 anos atrás

como resolver -4² + ( 3-5) x ( -2) ³ + 3² - ( -2) ao quadruplo

Respostas

respondido por: lelunardi1
2
 -4²   + ( 3-5) x ( -2) ³      + 3²   - ( -2)⁴  =
-4.-4 +  (-2)  x  (-2.-2.-2) + 3.3 - (-2.-2.-2.-2) =
 +16 +  (-2)  x   ( -8 )       +  9   - (+16) =
              \             /
 +16 +       (+16)  +9 -16 =
 +16 +16 +9 -16 =
    \      /      \     /
     +32         -7 =
           \         /
             +25
Perguntas similares